2020
DOI: 10.3389/fneur.2020.00785
|View full text |Cite
|
Sign up to set email alerts
|

A New Proposal for Severity Evaluation of Menière's Disease by Using the Evidence From a Comprehensive Battery of Auditory and Vestibular Tests

Abstract: To date, no widely accepted criteria exist to quantify the severity of Menière's disease (MD) by using vestibular tests. This study aimed to compare association of hearing loss and vertigo severity with association of accurate assessments of vestibular function and the vertigo severity. The severity of vertigo was documented by a comprehensive medical history with number of vertigo attacks in the past 6 months and a Dizziness Handicap Inventory (DHI) questionnaire. The involvement of vestibular organs was veri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 73 publications
(93 reference statements)
0
7
0
Order By: Relevance
“…A detailed scrutiny of symptoms has shown the existence of different subtypes or clinical variants in the unilateral (4) and bilateral (5) presentations of definite MD. This has also occurred in the case of bedside vestibular examination (6), auditory (7), and vestibular testing (8,9). MRI detection of EH is the result of high tech combined with complex sequence parametrization to allow the identification of the minute sensory and supporting structures of the inner ear within very hard dense bone.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed scrutiny of symptoms has shown the existence of different subtypes or clinical variants in the unilateral (4) and bilateral (5) presentations of definite MD. This has also occurred in the case of bedside vestibular examination (6), auditory (7), and vestibular testing (8,9). MRI detection of EH is the result of high tech combined with complex sequence parametrization to allow the identification of the minute sensory and supporting structures of the inner ear within very hard dense bone.…”
Section: Introductionmentioning
confidence: 99%
“…41 Alterations in cVEMP parameters, which vary from study to study, have also been reported in MD cases. Absent cVEMP was mentioned in SE and AE, 24 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 44 , 45 , 46 prolonged P1 and/or N1 latencies, 24 , 31 , 32 , 34 , 36 , 44 , 46 decreased inter-amplitude, 24 , 44 and altered asymmetry index. 33 , 35 , 47 …”
Section: Discussionmentioning
confidence: 88%
“…32 Altered oVEMP parameters have also been mentioned in MD, with variable results in the literature. Absent VEMP was mentioned in SE and AE, 30 , 33 , 34 , 35 , 36 as well as alterations in P1 and/or N1 latencies 32 , 34 , 36 , 46 and asymmetry index. 33 , 35 , 47 …”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations